Analisis Kesenjangan Program P5 melalui Risk Manajemen Worksheet Analys di SMP PGRI Candiroto dan SMP Negeri 1 Candiroto Kabupaten Temanggung - Syair, Muhammad; Murniati, Ngurah Ayu Nyoman; Soedjono, Soedjono (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
This research aims to find out (1) To analyze the gaps in the planning of the project to strengthen the profile of Pancasila students (P5) at driving and non-moving schools at SMP PGRI Candiroto and SMP Negeri 1 Candiroto, Temanggung Regency (2) To analyze the gap in the implementation of the project to strengthen the profile of Pancasila students (P5) at driving schools and non-movers at PGRI Candiroto Middle School and Candiroto 1 Middle School, Temanggung Regency. (3) To analyze the gaps in the evaluation of the project to strengthen the profile of Pancasila students (P5) at driving and non-moving schools at SMP PGRI Candiroto and SMP Negeri 1 Candiroto, Temanggung Regency This research uses a qualitative descriptive phenomenological approach design. The research subjects are SMP PGRI Candiroto as a driving school and SMP Negeri 1 Candiroto as a non-moving school. Data collection techniques include observation, interviews and documents. Data analysis through the process of data collection, data condensation, data presentation, and drawing conclusions. Test the validity of the data using credibility, transferability, dependability and confirmability tests. From the research results, it can be concluded that based on the gap analysis of the P5 program through risk management worksheet analysis at SMP PGRI Candiroto and SMP Negeri 1 Candiroto, Temanggungi Regency, the planning sub-focus was influenced by reflecting on mastery of identifying initial readiness in implementing P5. The sub-focus of implementation is influenced by helping students optimally throughout the project activities by encouraging student involvement with strategies for building bonds with students that are well carried out by the teacher. And the sub-focus evaluation gap is caused by a lack of teacher knowledge regarding the goals and principles of P5, and support from teachers other than as part of the P5 team.